2021
DOI: 10.1016/j.ebiom.2021.103575
|View full text |Cite
|
Sign up to set email alerts
|

E2A ablation enhances proportion of nodal-like cardiomyocytes in cardiac-specific differentiation of human embryonic stem cells

Abstract: Background: Human sinoatrial cardiomyocytes are essential building blocks for cell therapies of conduction system disorders. However, current differentiation protocols for deriving nodal cardiomyocytes from human pluripotent stem cells (hPSCs) are very inefficient. Methods: By employing the hPSCs to cardiomyocyte (CM) in vitro differentiation system and generating E2Aknockout hESCs using CRISPR/Cas9 gene editing technology, we analyze the functions of E2A in CM differentiation. Findings: We found that knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Furthermore, immunofluorescence staining showed a high expression level of cTNT in hiPSC‐CMs (Figure 1f). The expression profiles of pluripotency marker genes, including SOX2 , OCT4 , and NANOG , were assessed alongside mesoderm‐associated markers such as Brachyury T and ECOMES , cardiac mesoderm marker MESP1 , cardiac progenitor cell markers KDR , NKX2.5 , and ISL1 , and cardiomyocyte markers TNNT2 , MYH6 , and MYL7 during the differentiation of hiPSCs into cardiomyocytes (Figure 1g), which were consistent with previously reported observations (Li et al, 2021; Zhao, Wang, et al, 2020). These results indicated that our cardiac differentiation protocol was feasible.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, immunofluorescence staining showed a high expression level of cTNT in hiPSC‐CMs (Figure 1f). The expression profiles of pluripotency marker genes, including SOX2 , OCT4 , and NANOG , were assessed alongside mesoderm‐associated markers such as Brachyury T and ECOMES , cardiac mesoderm marker MESP1 , cardiac progenitor cell markers KDR , NKX2.5 , and ISL1 , and cardiomyocyte markers TNNT2 , MYH6 , and MYL7 during the differentiation of hiPSCs into cardiomyocytes (Figure 1g), which were consistent with previously reported observations (Li et al, 2021; Zhao, Wang, et al, 2020). These results indicated that our cardiac differentiation protocol was feasible.…”
Section: Resultssupporting
confidence: 89%
“…The differentiation of human induced pluripotent stem cells (hiPSCs) has made it feasible to generate cardiomyocytes with characteristics similar to cardiac pacemaker cells. Although the yield of SAN‐like pacemaker cells (SANLPCs) derived from current 2D cardiac‐specific differentiation protocols has shown significant improvements, it is important to acknowledge that these studies have not yet validated the biological pacemaking function of the obtained SANLPCs in animal models (Li et al, 2021; Liang et al, 2020; Liu et al, 2020; Ren et al, 2019; Yechikov et al, 2020). A previous study made a significant advancement in the effectiveness of generating SANLPCs from human pluripotent stem cells through the implementation of 3D differentiation protocol and flow cytometry sorting techniques.…”
Section: Introductionmentioning
confidence: 99%
“…TCF3, as transcription factor, plays an essential role in treating acute lymphoblastic leukemia, breast cancer, colorectal cancer, etc., and especially heart diseases. 15,[36][37][38] As the prediction of bioinformation analysis, TCF3 was suspected as a transcription factor of ATG5. ATG5 was essential in the early stage of autophagosome formation and development, cell differentiation, and maintenance of homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Besides, TCF3 was proved to play an essential role in heart development and cardiac-specific differentiation of human pluripotent stem cells. 15 Moreover, the overexpression of TCF3 in cardiomyocytes caused the disassembly of sarcomere, cell connection interruption, upregulation of immature markers, and a phenotype related to dedifferentiation of cardiomyocytes. 16 Meanwhile, TCF3 played an important role in heart formation.…”
Section: Introductionmentioning
confidence: 99%
“…Nodal signaling is vital for the formation of sinoatrial node. Nodal inhibition during the cardiac mesoderm differentiation stage downregulates PITX2c, a transcription factor recognized to inhibit the formation of the sinoatrial in the left atrium during cardiac development[ 19 ]. Moreover, nodal signaling is dispensable for initiation of heart looping; however, it regulates asymmetries that result in a helical shape at the heart tube poles[ 20 ].…”
Section: Signaling Pathways During Cardiogenesismentioning
confidence: 99%